Новейший справочник необходимых знаний: справочное издание / [сост.: Кондрашов А.П., Стреналюк Ю.В.] - А. П.
Экземпляры: ф.8 (20230518) / Инвентарный номер: 62260 / Цена: 50.00 / Авт.знак: Н 72 / ББК: 92